The influence of deoxygenation on Caribbean coral larval settlement and early survival - Mallon, Jennifer E.; Demko, Alyssa M.; Sneed, Jennifer M.; Newman, Lilyana; Dugan, Carle; Altieri, Andrew H.; Paul, Valerie Jean; Johnson, Maggie D. (Frontiers in Marine Science, 2023)
Deoxygenation is emerging as a major threat to coral reefs where it can have catastrophic effects, including mass coral mortality. Some coral species cannot survive more than a few days of exposure to low oxygen conditions, while others can tolerate deoxygenation for weeks, suggesting that coral tolerance to lowered dissolved oxygen (DO) concentrations is species-specific. However, hypoxia thresholds for corals have not yet been fully defined, and more information is needed to understand if tolerance to deoxygenation is consistent across all life stages. In this study, we tested the influence of severe (1.5 mg L-1 DO) and intermediate (3.5 mg L-1 DO) deoxygenation on larval settlement and survival during the early recruitment life phase of Colpophyllia natans, Orbicella faveolata, and Pseudodiploria strigosa. Exposure to deoxygenation over a 3-day settlement period did not significantly impact larval survival nor settlement rates compared to ambient DO concentrations (6 mg L-1 DO) for all three species. However, recruit survivorship in C. natans and O. faveolata after further exposure to severe deoxygenation was reduced compared to intermediate deoxygenation and control DO conditions. After 45 days of exposure to severe deoxygenation only 2.5 ± 2.5% of the initial O. faveolata had survived the larval and recruit stages compared to 22.5 ± 4.5% in control oxygen conditions. Similarly, C. natans survival was 13.5 ± 6.0% under severe deoxygenation, compared to 41.0 ± 4.4% in the control treatment. In contrast, survival of P. strigosa larvae and recruits was not different under deoxygenation treatments compared to the control, and higher overall, relative to the other species, indicating that P. strigosa is more resilient to severe deoxygenation conditions during its earliest life stages. This study provides unique insights into species-specific variation in the tolerance of coral recruits to deoxygenation with implications for whether this life history stage may be a demographic bottleneck for three ecologically important Caribbean coral species. Given the increasing frequency and severity of deoxygenation events in Caribbean coastal waters, these results are an important contribution to the growing body of research on deoxygenation as a threat to coral reef persistence in the Anthropocene, with implications for conservation and restoration efforts integrating coral recruitment into reef recovery efforts.